The Italian, Volume 1 (of 3) - Radcliffe, Ann Ward, 1764-1823 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Italian, Volume 1 (of 3): or, the confessional of the Black Penitents" by Ann Radcliffe is a Gothic novel published in 1796. When young Vivaldi falls for the beautiful but poor Ellena, his aristocratic mother enlists her sinister confessor, Father Schedoni, to destroy the match. What follows is a dark tale of kidnapping, disguise, and persecution set against the backdrop of the Inquisition, where mysterious monks issue warnings, convents imprison innocents, and shocking secrets threaten to surface in shadowy confessionals. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Italian_(Radcliffe_novel)
Release date is 2024-10-27
Delphine Lettau and the online Distributed Proofreaders Canada team at pgdpcanada.net from images generously made available by Internet Archive/European Libraries
Keywords: Horror tales; Love stories; Gothic fiction; Kidnapping -- Fiction; Inquisition -- Fiction; Naples (Italy) -- Fiction; Monks -- Italy -- Fiction